CMR for characterization of the myocardium in acute coronary syndromes. - Dall'Armellina, E; Karamitsos, T; Neubauer, S; Choudhury, R (2010)
The utility of cardiac magnetic resonance imaging (CMR) as a diagnostic technique is well established. CMR enables tissue characterization, distinction between myocardial scar tissue and viable tissue, and evaluation of myocardial perfusion and contractile function. To date, CMR has been mostly applied in the assessment of stable disease; however, a role for CMR in the acute setting is also emerging. An accurate appraisal of the myocardium with CMR in the first hours after the onset of chest pain could provide supporting information to standard diagnostic tools, such as electrocardiography and measurement of blood biomarkers, which could help guide the selection of appropriate treatment. The aims of this integrated approach include positive identification of an ischemic syndrome, estimation of downstream areas at risk of damage, evaluation of epicardial artery patency and small vessel integrity, quantification of infarct size, and determination of myocardial function. This Review critically evaluates both established and emerging CMR techniques, and relates the imaging findings to the underlying pathophysiological processes in acute coronary syndromes. A more thorough understanding of CMR techniques will clarify their potential clinical applications and limitations, and assess the practicality of CMR in the setting of acute coronary syndromes, where early intervention is crucial to save myocardium at risk of irreversible injury.